A specific pi-ligand transfer reaction via triple-decker sandwich complex intermediates - Bohm, D.; Heinemann, Frank Wilhelm; Hu, D. Q.; Kummer, S.; Zenneck, Ulrich (Collection of Czechoslovak Chemical Communications, 1997)
Photochemically generated cationic cyclopentadienyl iron fragments [FeCp](+) allow a specific stacking reaction of [(t-Bu(3)C(3)P(2))Fe(t-Bu(2)C(2)P(3))]. This results in the transient formation of an unstable cationic Fe-Fe triple-decker sandwich complex which decomposes by deliberating the neutral sandwich complex [CpFe(t-Bu(2)C(2)P(3))], and is stacked again by a second [FeCp](+)-unit, yielding the moderately stable cationic triple-decker sandwich complex [CpFe(t-Bu(2)C(2)P(3))FeCp](+) with a central mu-eta(5):eta(5)-triphospholyl ligand. Air exposure or storage of solutions at room temperature leads to a destacking and the neutral triphosphaferrocene derivative [CpFe(t-Bu(2)C(2)P(3))] is formed again almost quantitatively in respect to the pentaphospha-ferrocene educt.
Keywords: iron compounds; triple-decker sandwich complexes; triphospholyl complexes